An analysis of physical fitness during pre-competitive phase among young athletes / Syaiditina Aisyah ... [et al.]. - Aisyah, Syaiditina; Shari, Maisarah; Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat (2024)
The pre-competitive phase represents a crucial period in an athlete’s training cycle, during which the emphasis transitions from building foundational fitness to refining specific skills and optimizing overall physical performance. Young athletes require customized training strategies to enhance their physical fitness, preparing them for the rigours of competition and enabling them to excel in their respective sports. This study aims to evaluate the physical fitness levels of young athletes during the pre-competitive phase, offering insights into the efficacy of current training practices and pinpointing areas for potential improvement. A total of 209 SUKMA athletes participated in this study, undergoing five fitness tests designed to measure various aspects of their physical fitness: body mass index (BMI), sit-and-reach test, Yo-Yo endurance test (YYET), countermovement jump test (CMJ), and one-minute push-up test. These assessments were conducted before and after the athletes’ preparatory phase to evaluate changes in BMI, flexibility, cardiovascular endurance, muscular power, and muscular endurance. The results revealed significant differences in muscular power, flexibility, muscular endurance, and cardiovascular endurance (p < 0.001) between the pre-and post-testing phases. However, BMI did not show any significant changes. These findings highlight the effectiveness of the pre-competitive training phase in enhancing key physical fitness components, although BMI remained unaffected. Future research should focus on further elucidating strategies to optimize young athletes’ physical health and performance during this pivotal pre-competitive period, ensuring they are adequately prepared for competition demands.